The role of chemotherapy in the treatment of advanced appendiceal cancers: summary of the literature and future directions. (July 2022) - Strach, Madeleine C.; Sutherland, Sarah; Horvath, Lisa G.; Mahon, Kate
Appendiceal cancer is rare and encompasses a diverse group of tumours ranging from low-grade appendiceal mucinous neoplasms to high-grade adenocarcinomas. Appendiceal cancers often spread to the peritoneal cavity causing extensive mucinous dissemination and peritoneal metastases. Prognosis varies with histological subtype. Cytoreductive surgery and heated intraperitoneal chemotherapy is well-established as the most effective treatment achieving long-term survival in some patients. Chemotherapy regimens used to treat appendiceal cancer are extrapolated from the colorectal cancer setting, but disease biology differs and outcomes are inferior. The role of chemotherapy in the treatment of appendiceal cancer remains poorly defined. There is an urgent need to develop novel tailored treatment strategies in the perioperative and unresectable setting. This review aims to evaluate the literature for patients who received intraperitoneal and systemic chemotherapy for appendiceal cancers.